Pengaruh Model Pembelajaran Blended Learning Terhadap Keaktifan Belajar Siswa Kelas IV SD Se-Gugus Ahmad Yani Kecamatan Majenang - Damayanti, Shinta; Sari, Fita Permata (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Student learning activity is very important and affects the character of students. This study aims to determine the influence of blended learning models on students' learning activity. This research uses quantitative approach with experimental method. The population in this study was grade IV elementary school students in Ahmad Yani group of 195 with a sample of 61 students. Data collection techniques using questionnaires. The validity test of the instrument used is the validity of the contents and look for different power using the product moment correlation formula. Instrument reliability using the Alpha Cronbach formula. The prerequisite test of the analysis conducted is a test of normality and homogeneity.The results prove that blended learning model has a significant effect on students' learning activity. This can be indicated by a sig value of 0.001 ≤ 0.05.